The Effect Intellectual Capital on Sharia Companies Financial Performance in Two Countries in 2012-2016 - Dewi, Karina Chandra; Khoiruddin, Moh (Universitas Negeri Semarang, 2019)
Abstract The purpose of this study is to determine whether there is influence or not intellectual capital on the financial performance of sharia companies JII Indonesia and BMHSI Malaysia. The research samples is 28 JII companies and 6 BMHSI companies in 2012-2016. The data analysis method used in this study is multiple regression analysis. The results showed that the VACA variable regression coefficient was 12,232 with a sig value of 0,000 on JII and 2,112 with a sig value of 0,045 on BMHSI; VAHU variable regression coefficient of 2.841 with a sig value of 0.005 on JII and 5.591 with a sig value of 0.000 on BMHSI; and STVA variable regression coefficient of 1.874 with a sig value of 0.063 on JII and -0.505 with a sig value of 0.618 on BMHSI. The conclusion of this study is that VACA and VAHU have a positive and significant effect on the financial performance of sharia JII companies as well as BMHSI and STVA which have a negative and not significant effect on the financial performance of sharia companies JII and BMHSI.